Treatment Outcome and Associated Factors of Acute Malnutrition Among Children in the Therapeutic Feeding Center of Public Hospitals in Addis Ababa, Ethiopia: An Institutional-Based Cross-Sectional Study - Mezemir M; Girma M; Bekele D (Dove Medical Press, 2022)
Melat Mezemir,1 Meskerem Girma,2 Dereje Bekele3 1Saint Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2College of Health and Medical Science, Bahir Dar University, Bahir Dar, Ethiopia; 3Oromia Regional Health Bureau, Addis Ababa, EthiopiaCorrespondence: Melat Mezemir, Email melderatnahil24@gmail.comBackground: Severe acute malnutrition is the most prevalent reason for admission to a pediatric unit, and it is a leading cause of mortality in many countries, including Ethiopia, at 25% to 30%, where it affects both developed and developing countries. The objective of this study was to assess treatment outcomes and associated factors among children aged 6- 59 months with severe acute malnutrition.Methods: A cross-sectional study was conducted using secondary data from medical records of patients enrolled in the therapeutic feeding center from January 2016 to March 2019. There were 385 samples collected at 3 public referral hospitals in Addis Ababa, which were selected by simple random sampling. A structured questionnaire was used to collect data from the available individual folders and registers. The data analysis was performed using binary and multivariable logistic regression models. The odds ratio with 95% CI was used to identify predictor variables. Variables that have a p-value < 0.05 were considered significant.Results: Children who had tuberculosis were 79% less likely to recover than those who had no tuberculosis. In this study, deaths accounted for 9.1%, recovered were 72.2%, and defaulters accounted for 11.6% with a mean length of stay of 18.6 (CI: 16.9, 20.2) days and an average weight gain of 7.2 g/kg/day (CI: 5.7, 8.2).Conclusion: Treating comorbidities on time can help children to recover early and reduce readmission. Integration of severe acute malnutrition screening into all service delivery points can help early identification and treatment. In the meantime, treating them with ready-to-use therapeutic feeding has a significant change in recovery.Keywords: severe acute malnutrition, length of hospital stay, treatment outcome, Ethiopia